Burial, Accretion, and Exhumation of the Metamorphic Sole of the Oman‐UAE Ophiolite. Issue 4 (13th April 2021) - Ambrose, T. K.; Waters, D. J.; Searle, M. P.; Gopon, P.; Forshaw, J. B.
Abstract: We conducted petrological analyses of samples collected across a 250‐m thick section of the metamorphic sole of Oman‐United Arab Emirates ophiolite. Thermobarometric calculations on garnet‐clinopyroxene amphibolites (retrogressed granulites) from the top 85 m of sole indicate peak pressure‐temperature conditions of 700°–900°C and 10–12 kbar, corresponding to depths of 30–40 km. Structurally lower (85–250 m below peridotite) epidote amphibolites record similar pressures, but temperatures that are ∼100°C lower. We document progressive retrogression of the peak granulite facies assemblage down through amphibolite and greenschist facies pressure‐temperature conditions. We propose that pervasive granulite formation in metabasic rocks along the top of the downgoing slab resulted in rheological strengthening that caused the subduction interface to migrate downwards and accrete a slice (the high‐temperature sole) to the hanging‐wall mantle. Structurally lower thrust slices of epidote and bimineralic amphibolites, as well as interlayered metasedimentary rocks, were subsequently underplated at similar pressures of 10–12 kbar, but lower temperatures, as the subduction zone cooled. Prograde metamorphism of these lower‐grade thrust slices released fluids that (re)hydrated the overlying granulites and hanging‐wall peridotites. Along with several other recent studies, our results indicate that the base of the ophiolite and the granulite‐amphibolite facies part of the metamorphic sole were juxtaposed at depths of 30–40 km. Our results are consistent with other observations from the metamorphic sole and base of the ophiolite that indicate the sole was exhumed along a flattening slab. Key Points: We document progressive retrogression of a granulite facies assemblage in the metamorphic sole of the Oman‐UAE ophiolite Development of the granulite facies assemblage led to rheological strengthening and underplating of the metamorphic sole Hydrous fluids released from subsequently underplated thrust sheets hydrated the overlying granulites and hanging‐wall mantle peridotite